polyarylene sulfide film
Patent Information
- Application Number
- KR1020237008842
- Authority / Receiving Office
- KR · KR
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2021-03-29
- Filing Date
- 2021-09-21
- Publication Date
- 2026-10-13
- Estimated Expiration
- 2041-09-21
Smart Images

Figure 112023028810413-PCT00001 
Figure 112023028810413-PCT00002 
Figure 112023028810413-PCT00003
Abstract
Description
Technology Field
[0001] The present invention relates to a polyarylene sulfide film. Background Technology
[0002] Recently, glass has been considered as a material for circuit boards requiring transparency. However, glass substrates have drawbacks such as being brittle, heavy, and difficult to thin; furthermore, they lacked sufficient materials for flexibility in applications such as car windshields or parts that come into contact with curved surfaces inside and outside the vehicle.
[0003] Polyarylene sulfide resins possess excellent properties such as heat resistance, flame retardancy, rigidity, chemical resistance, electrical insulation, and low moisture absorption, making them particularly suitable for use in electrical and electronic devices, mechanical parts, and automotive components. In the field of electrical and electronic components, the trend toward high speed and high capacity demands materials with low transmission loss. Polyarylene sulfide films, represented by polyphenylene sulfide (hereinafter abbreviated as PPS) films, are being applied as circuit materials by leveraging their high transmission loss and low moisture absorption. However, because PPS films have low transparency and inferior color tone, visibility is prone to deterioration due to factors such as transparency and color tone when used, for example, as transparent circuit boards; thus, improvements in transparency and color tone are desired.
[0004] Until now, there has not been sufficient consideration of techniques for improving color tone in PPS films. For example, a technique of applying a rubbing treatment to a PPS film to improve transparency and slipperiness has been disclosed (Patent Document 1). In addition, a technique for reducing the content of impurities generated as by-products during the polymerization reaction and improving volatile matter and color tone has been disclosed (Patent Document 2). Prior art literature
[0005] Japanese Patent Publication No. 2013-67748 Japanese Patent Publication No. 2009-138206 The problem to be solved
[0006] However, the technology described in Patent Document 1 had the problem that it was insufficient to improve the color tone of the PPS resin. In addition, the technology described in Patent Document 2 had the problem that it was not transparent when applied to film applications.
[0007] The objective of the present invention is to solve the aforementioned problems. That is, to provide a polyarylene sulfide film having excellent transparency and color tone. means of solving the problem
[0008] The polyarylene sulfide film of the present invention has the following configuration to solve the above problem. That is, it is a polyarylene sulfide film having a polyarylene sulfide (PAS)-based resin as the main component, a spectral light transmittance Ta of 75% or more at a wavelength of 550 nm, and a b value of 5.0 or less. Effects of the invention
[0009] The polyarylene sulfide film of the present invention has excellent transparency and color tone. Therefore, taking advantage of these characteristics, it can be suitably used as various components requiring transparency, such as automotive components, battery components, display components, industrial packaging materials, decorative materials, and electrical and electronic materials, for example, transparent circuit boards, transparent antenna boards, transparent circuit boards for high frequency, and transparent antenna boards for high frequency. Specific details for implementing the invention
[0010] In the present invention, the polyarylene sulfide film is a film formed as a sheet by melt-molding a resin composition having a polyarylene sulfide (hereinafter PAS) resin as the main component, and preferably, it may be biaxially stretched and heat-treated.
[0011] In the present invention, the phrase "having a PAS-based resin as a main component" means including a PAS-based resin in an amount of 50 mass% or more, preferably 60 mass% or more, and more preferably 70 mass% or more. If the content of the PAS-based resin is less than 50 mass%, the heat resistance, dimensional stability, and mechanical properties characteristic of the PAS film may be impaired.
[0012] The PAS-based resin used in the present invention is a copolymer having repeating units of -(Ar-S)-. As Ar, units represented by the following formulas (A) to (K) may be used.
[0013]
[0014] (R1 and R2 are substituents selected from hydrogen, alkyl groups, alkoxy groups, and halogen groups, and R1 and R2 may be the same or different)
[0015] Among the above formulas, the p-arylene sulfide unit is preferred as the repeating unit. Representative examples include polyphenylene sulfide, polysulfone, polyethersulfone, polyphenylene sulfide sulfone, and polyphenylene sulfide ketone. In particular, the p-arylene sulfide unit is exemplified as a preferred p-arylene sulfide unit from the perspective of film properties and economic feasibility.
[0016] The polyarylene sulfide-based resin used in the present invention preferably comprises p-phenylene sulfide units represented by the following structural formula as major constituent units, in an amount of 80 mol% or more and 99.9 mol% or less of the total repeating units. By using the PAS-based resin used in the present invention with the above composition, excellent heat resistance and chemical resistance can be achieved.
[0017]
[0018] In addition, the PAS-based resin used in the present invention may copolymerize with copolymerization units in a range of 0.01 mol% or more and 20 mol% or less of repeating units.
[0019] Preferred copolymer units may be the following, and a particularly preferred copolymer unit is an m-phenylene sulfide unit.
[0020]
[0021]
[0022]
[0023] (Here, X represents the alkylene, CO, and SO2 units)
[0024]
[0025]
[0026] (Here, R represents an alkyl, nitro, phenylene, or alkoxy group)
[0027] Regarding the main constituent unit of the PAS-based resin used in the present invention, the mode of copolymerization with the copolymerization unit is not particularly limited, but it is preferred to be a random copolymer.
[0028] The PAS-based resin composition constituting the PAS film of the present invention may contain various additives, such as antioxidants, heat stabilizers, antistatic agents, or anti-blocking agents, within a range that does not impair the effects of the present invention.
[0029] The PAS film of the present invention must have a light transmittance (Ta) of 75% or more at a wavelength of 550 nm. By making Ta 75% or more, a film with excellent transparency is obtained. If Ta is less than 75%, the cloudiness of the film increases, and transparency may decrease when used as a protective substrate for a transparent circuit board or an optical component. The light transmittance at a wavelength of 550 nm is more preferably 78% or more, and even more preferably 80% or more. To achieve the light transmittance at a wavelength of 550 nm within the above range, methods such as controlling particles or other resins contained in the film for runnability, described later, or removing impurities by performing a cleaning treatment with a solvent on the polymer after polymerization or the obtained film, described later, may be used.
[0030] The PAS film of the present invention preferably satisfies the following equation (i) for a light transmittance (Tb) at a wavelength of 400 nm and a light transmittance (Tc) at 600 nm.
[0031] Tc-Tb≤8.2% Equation (i)
[0032] By possessing the above characteristics, it indicates that there are few impurities that absorb light in the wavelength range of 400 nm to 600 nm, and a film with low coloration is obtained. In addition, if Tc-Tb exceeds 8.2%, there may be coloration when used as a substrate material, resulting in a decrease in color tone. More preferably, Tc-Tb ≤ 8.0%. To keep Tc-Tb within the above range, it can be controlled by reducing residual impurities in the PAS film through the cleaning treatment described later. In the present invention, impurities refer to substances that absorb light in the range of 400 to 600 nm, such as N-methyl-2-pyrrolidone (NMP), a polymerization solvent, sodium hydrogen sulfide (NaSH), a byproduct of polymerization, and 4-chlorobenzene thioleate. The light transmittance at wavelengths of 550 nm, 400 nm, and 600 nm can be evaluated by the method described later.
[0033] The PAS film of the present invention requires that the b value, which is an indicator of yellowness, be 5.0 or less. By making the b value 5.0 or less, a film with excellent color tone is obtained. If the b value exceeds 5.0, when used as a protective substrate for a transparent circuit board or an optical member, visibility may deteriorate due to color tone factors, leading to the overlooking of defects. More preferably, it is 3.0 or less, even more preferably 2.5 or less, and most preferably 2.0 or less. Although a lower limit is not specifically determined, it is preferable that it be 0.0 or greater from the perspective of productivity. To obtain a polyarylene sulfide film with a b value within the above range, methods such as removing impurities by performing a solvent cleaning treatment on the polymer after polymerization or the obtained film, as described below, may be used.
[0034] The PAS film of the present invention preferably has an L value, which is an indicator of brightness, of 85 or higher. By setting the L value to the above range, a film with excellent color tone is obtained. If the L value is less than 85, the brightness is low when used as a protective substrate for a transparent circuit board or an optical member, which may result in poor visibility. More preferably, it is 90 or higher. To obtain a PAS film with an L value within the above range, control can be achieved by controlling particles or other resins contained in the film as described below, or by the lamination configuration of the film as described below. The L value can be evaluated by the method described below.
[0035] The cleaning treatment in the present invention is a process of immersing a polymer powder or a film obtained by melt-molding the polymer to form a sheet and performing biaxial stretching heat treatment in a solvent while heating for a predetermined period of time. In the present invention, the polymer powder may be obtained by a method of reacting an alkali metal sulfide, such as sodium sulfide, with a polyhalo-aromatic compound, such as p-dichlorobenzene, in an organic amide solvent such as NMP (Japanese Patent Publication No. Sho 45-3368), but is not particularly limited. In particular, a method of cleaning the polymer powder obtained by polymerization with a solvent is preferred from the perspective of productivity and efficiency.
[0036] Cleaning solvents used in cleaning treatment include, for example, acetone, toluene, and NMP, and are particularly used as polymerization solvents, and NMP is preferred from the perspective of removing residual impurities.
[0037] Next, the present invention will be described using a cleaning method using NMP as an example, but the present invention is not limited thereto.
[0038] In the present invention, the temperature of the solvent during cleaning is preferably 100°C or higher and 200°C or lower. By setting the cleaning temperature within the above range, the temperature is above the glass transition temperature of the resin, and since molecular chain movement is initiated, residual impurities can be efficiently removed, resulting in a film with excellent transparency and color tone. If the temperature is below 100°C, the molecular chains are constrained, so impurities remain, which may lead to a decrease in color or color tone. Furthermore, if the temperature exceeds 200°C, the mobility of the resin becomes excessively high, so extracted impurities are reintroduced into the resin, which may lead to a decrease in color or color tone. More preferably, the temperature of the solvent during cleaning in the present invention is 125°C or higher and 175°C or lower.
[0039] In the present invention, it is preferable that the solvent cleaning treatment time be 5 hours or more. By setting the treatment time during cleaning to the above range, the deterioration of the solvent can be suppressed and impurities can be efficiently removed. If it is less than 5 hours, impurities may not be extracted, and discoloration or color tone may deteriorate. The upper limit of the treatment time is not particularly limited, but from the perspective of productivity, it is 30 hours or less. More preferably, the treatment time during cleaning in the present invention is 10 hours or more, and even more preferably 20 hours or more.
[0040] In addition, in the present invention, it is preferable to include fine bubbles in the cleaning solvent. In the present invention, fine bubbles are bubbles with a diameter of 100 μm or less. The method of including fine bubbles in the cleaning solvent is not particularly limited, but for example, a known apparatus exemplified in Japanese Patent Publication No. 2007-21343 may be used. By including fine bubbles in the solvent, the wettability of the cleaning solvent toward the polymer powder or film is increased, and penetration becomes easier, thereby obtaining an efficient cleaning effect. Examples of gas species included in the fine bubbles are nitrogen (N2), oxygen (O2), carbon dioxide (CO2), etc., but any of them may be used. In particular, oxygen is preferred to promote adsorption through interaction with the functional groups of the resin.
[0041] The PAS film of the present invention preferably has a surface roughness (Ra) of at least one film surface of 10 nm or more and 200 nm or less. SRa is a parameter of three-dimensional surface roughness, and refers to the average roughness at the center plane when the surface roughness curve is approximated by a sine curve, and is defined as the center plane average roughness. The center plane average roughness is a three-dimensional extension of the centerline average roughness (Ra) of the two-dimensional roughness parameters described in JIS-B0601-1994, and is calculated by dividing the volume of the part enclosed by the surface shape curve and the center plane by the measured area. When the center plane is the XY plane, the longitudinal direction is the Z-axis, and the measured surface shape curve is f(x, y), it is defined by the following equation (ii). Here, Lx is the measured length in the X direction and Ly is the measured length in the Y direction.
[0042]
[0043] By setting SRa to the above range, a film with excellent runability is obtained. If the surface roughness (Ra) of the film surface is less than 10 nm, the surface is smooth, so friction during transport increases, which may lead to a decrease in runability. If the surface roughness (SRa) of the film surface exceeds 200 nm, light reflection occurs due to surface irregularities, which may lead to a decrease in transparency. More preferably, the surface roughness (SRa) of the film surface is 10 nm or more and 100 nm or less, and more preferably 20 nm or more and 50 nm or less. To set the surface roughness (SRa) of the film surface to the above range, it can be controlled by particles or other resins contained in the film described later, and also by the lamination configuration of the film described later. The surface roughness (SRa) of the film surface can be evaluated by the method described later.
[0044] The PAS film of the present invention has a depth volume (Vv) from a reference surface on at least one film surface of 50 μm. 3 800㎛ or more 3 It is preferable that it be as follows. In the present invention, depth volume (Vv) is the sum of the volumes of each depression from a reference plane within one field of view, measured by a VertScan manufactured by Mitsubishi Chemical Systems, Inc. based on the measurement method described below. In the present invention, the reference plane refers to a hand surface where the depth volume and the protrusion volume are equal, and is a plane automatically set by the VertScan analysis software. A smaller depth volume (Vv) indicates that the depression of the film surface is small.
[0045] By setting the depth volume (Vv) to a range below the upper limit mentioned above, the film surface may have minimal depression and excellent surface quality, and by setting the depth volume (Vv) to above the lower limit mentioned above, excessive friction during transport may be suppressed and good runability during processing may be achieved. More preferably, the depth volume (Vv) is 100㎛.3 600㎛ or more 3 It is less than or equal to, and more preferably 150 μm 3 400㎛ or more 3 The following applies. To achieve a depth volume (Vv) of the film surface within the above range, it can be obtained by a method of control using particles or other resins contained in the film described below, or by a method of control using the laminated configuration of the film described below. The depth volume (Vv) of the film surface can be evaluated by the method described below.
[0046] The PAS film of the present invention has a depth volume (Vv) (unit: μm) from a reference plane on at least one film surface. 3 It is desirable that the number of protrusions (n) (unit: number of) satisfies the following formula (iii). In the present invention, the number of protrusions is the number of protrusions per field of view obtained when the threshold is measured by VertScan and the reference plane is used.
[0047] 0.01≤Vv / n≤3.0 Equation (iii)
[0048] Vv / n represents the depth volume for a single protrusion; for example, in the case where scratches exist on the film surface, Vv / n tends to increase in the case of scratches with large irregularities, and tends to decrease in the case of scratches with small irregularities. By setting Vv / n above the above lower limit, excessive friction during transport can be suppressed, and runability during processing can be improved. Furthermore, by setting Vv / n below the above upper limit, surface quality can be improved. Vv / n is more preferably 0.1 μm 3 / more than 1.5㎛ 3 / piece or less, more preferably 0.1㎛ 3 / more than 0.5㎛ 3It is less than or equal to / . To keep Vv / n within the above range, it can be controlled by particles or other resins contained in the film described below, or by the laminated configuration of the film described below. Vv / n can be evaluated by the method described below.
[0049] Preferably, the PAS film of the present invention has a glossiness of 140% or more and less than 200% on at least one film surface. By setting the glossiness to the above range, surface irregularities that optically diffusely reflect light from the surface are reduced, resulting in high surface smoothness. When a metal layer is formed by deposition, sputtering, plating, etc., for use as a circuit, surface irregularities are less likely to occur, making it possible to obtain a circuit with excellent transmission characteristics. Additionally, when a metal layer is formed by deposition or sputtering for use as a reflective film, surface irregularities of the metal layer are less likely to occur. By keeping the glossiness below the upper limit mentioned above, it is possible to suppress the deterioration of transmission characteristics or reflection efficiency caused by excessively large surface irregularities and the metal layer transferring the surface irregularities of the film. Furthermore, by keeping the glossiness above the lower limit mentioned above, it is possible to suppress the deterioration of runability during processing caused by excessively smooth surface, which increases friction during transport.
[0050] The PAS film of the present invention contains particles and / or dispersions, and it is preferable that the void formation ratio of said particles and dispersions is 10% or less. In the present invention, the void formation ratio refers to the ratio of particles and dispersions that form voids having a size of 10% or more of the cross-sectional area of the particles or dispersions in the FE-SEM image of the cross-section of the film, and refers to a value measured by the method described below. By setting the void formation ratio to the above range, it becomes possible to suppress light diffusion and light reflection within the film, suppress the deterioration of the film's transparency, and improve the color tone. More preferably, the void formation ratio is 5.0% or less, and even more preferably 3.0% or less. Methods for setting the void formation ratio to the above range may include control by particles or other resins contained in the film described below, or by the lamination configuration of the film described below.
[0051] To control the surface characteristics of the film described above, there are methods of controlling the surface by incorporating inert particles into the PAS film, or by incorporating a different thermoplastic resin (X) distinct from the PAS-based resin. When incorporating inert particles, examples of inorganic particles such as silica, alumina, calcium carbonate, barium carbonate, barium titanate, barium sulfate, calcium silicate, magnesium oxide, titanium oxide, and zinc oxide may be used. When incorporating a different thermoplastic resin, polyarylate, polyphenylene ether, polyetherimide, polysulfone, polyphenylsulfone, and polyethersulfone may be used; however, polysulfone, polyphenylsulfone, and polyethersulfone are preferably used from the perspective of affinity with the PAS-based resin. In the present invention, the method of incorporating a different thermoplastic resin is preferred from the perspective of achieving transparency, color tone, and runability.
[0052] The PAS film of the present invention has an infrared absorption spectrum of 1145 cm⁻¹ obtained by Fourier transform infrared spectroscopy (FT-IR). -1~1160 cm -1 It is desirable to have at least one absorption peak in the range. The absorption peak in the above range refers to a peak originating from the stretching vibration of the S=O bond, and since the affinity between the PAS-based resin and the thermoplastic resin (X) is increased, transparency is obtained because it is finely and uniformly dispersed within the PAS-based resin, and also surface roughness can be imparted by the thermoplastic resin (X), thereby obtaining a film that is compatible with runnability. To have an absorption peak in the above range, it can be achieved by including a resin having sulfonic acid groups, such as polysulfone, polyphenylsulfone, or polyethersulfone, in the thermoplastic resin (X) at a predetermined concentration.
[0053] The PAS film of the present invention contains W of a PAS-based resin. Ⅰ As, the content W of a thermoplastic resin (X) different from the PAS-based resin. Ⅱ When the total is 100 parts by mass, the content W of the thermoplastic resin (X) Ⅱ It is preferable that the amount is 0.01 parts by mass or more and 5.0 parts by mass or less. To achieve both drivability and transparency, it is more preferable that the content W of the thermoplastic resin (X) is Ⅱ The amount is 0.2 parts by mass or more and 1.0 parts by mass or less. By keeping the content of the thermoplastic resin (X) below the upper limit described above, the deterioration of transparency due to the difference in the refractive index of the resin can be suppressed. In addition, the content W of the thermoplastic resin (X) Ⅱ By making it above the lower limit mentioned above, it is possible to prevent the deterioration of the quality caused by poor runability during filming.
[0054] The PAS film of the present invention preferably has two or more layers having a PAS-based resin as the main component, and at least one outermost layer is a layer (Layer A) having a PAS-based resin as the main component and containing at least one other thermoplastic resin (X) that is different from the PAS-based resin. By configuring two or more layers, multiple characteristics such as transparency, color tone, runability, and surface quality can be combined. As for the laminated configuration, when the layer having a PAS-based resin as the main component is Layer B, multilayer configurations such as A / B, A / B / A, A / B / A / B, and A / B / A / B / A can be cited.
[0055] The PAS film of the present invention has three or more layers having a PAS-based resin as the main component, and it is preferable that the outermost layer of both sides is a layer (Layer A) having a PAS-based resin as the main component and containing at least one other thermoplastic resin (X) different from the PAS-based resin, in order to be controllable while possessing multiple characteristics. As a laminated configuration, multilayer configurations such as A / B / A and A / B / A / B / A can be cited. In the present invention, a three-layer configuration of A / B / A is more preferable from the perspective of transparency, color tone, surface quality, and drivability.
[0056] The PAS film of the present invention has an A layer at 1145 cm⁻¹ in the infrared absorption spectrum obtained by Fourier Transform Infrared Spectroscopy (FT-IR). -1 ~1160 cm -1 It is desirable to have at least one absorption peak in between.
[0057] In the PAS film of the present invention, in the A layer, it is preferable that a thermoplastic resin (X) different from the PAS-based resin is incompatible with the PAS-based resin and is included as a dispersion within the PAS-based resin. In the present invention, the statement that a thermoplastic resin (X) different from the PAS-based resin is incompatible with the PAS-based resin and is included as a dispersion within the PAS-based resin indicates that a sea-island structure is formed by the PAS-based resin and the thermoplastic resin (X) different from the PAS-based resin, and that the PAS-based resin constitutes the sea component and the thermoplastic resin (X) different from the PAS-based resin constitutes the island component. By having a dispersion incompatible with the PAS-based resin in the A layer, which has the PAS-based resin as the main component, surface irregularities can be formed and controlled, thereby obtaining a film with excellent transparency, drivability, and quality. In addition, the shape of the dispersion is not particularly limited. The shape can be confirmed by observing the cross-section of the film using a transmission electron microscope (TEM) or a scanning electron microscope (SEM), and examples include circular, elliptical, spindle-shaped, and irregular shapes.
[0058] The PAS film of the present invention preferably has an aspect ratio of the dispersion obtained by the measurement method described below, which is 5.0 or higher and 15.0 or lower. In the present invention, the aspect ratio refers to a value calculated from the ratio of the major axis to the minor axis in the dispersion diameter of the thermoplastic resin (X) present as a dispersed phase in the PAS-based resin. An aspect ratio within the above range indicates that the interaction between the PAS-based resin and the thermoplastic resin (X) is strong. Therefore, it is desirable because it prevents the formation of voids, which are a factor in the deterioration of transparency during the stretching process, and allows for the improvement of transparency. By setting the aspect ratio of the dispersion above the lower limit described above, it is possible to suppress the deterioration of transparency caused by the formation of voids during the stretching process. On the other hand, by setting the aspect ratio of the dispersion below the upper limit described above, it is not necessary to use conditions that extremely increase the stretching ratio, thereby suppressing the deterioration of productivity caused by breakage during the film-making process. More preferably, the lower limit of the aspect ratio is 7.0 or higher. The upper limit of the aspect ratio is more preferably 12.0 or less, and more preferably 10.0 or less. The aspect ratio can be controlled by the stretching ratio among the film formation conditions described below.
[0059] In the PAS film of the present invention, the major axis of the dispersion is preferably 200 to 2000 nm. This is desirable because setting the major axis of the dispersion within this range allows for the formation of surface irregularities, thereby improving runability and surface quality. By setting the major axis of the dispersion above the lower limit described above, the formation of surface irregularities is reduced, resulting in a smoother surface; consequently, friction during transport increases, which can suppress the deterioration of runability and surface quality. On the other hand, by setting the major axis of the dispersion below the upper limit described above, the deterioration of transparency caused by light diffusion by the dispersion can be suppressed. More preferably, the major axis of the dispersion is 400 to 1000 nm. The major axis of the dispersion can be controlled by the stretching ratio among the film-forming conditions described later. In the present invention, the major axis of the dispersion can be calculated by the method described later.
[0060] In the PAS film of the present invention, it is preferable that the thickness ratio of the A layer is 0.1% or more and 10% or less relative to the total thickness of the film. It is desirable to set the thickness ratio of the A layer within the above range so that surface irregularities can be formed densely and the amount of dispersion in the entire film can be reduced, thereby improving transparency, color tone, and surface quality. By setting the thickness ratio of the A layer above the lower limit described above, the formation of surface irregularities is reduced and the surface becomes smooth, which can suppress the deterioration of runability and surface quality caused by increased friction during transport. Furthermore, by setting the thickness ratio of the A layer below the upper limit described above, surface irregularities are formed densely, resulting in excellent transparency. More preferably, the thickness ratio of the A layer is 0.5% or more and 5.0% or less, and more preferably 1.0% or more and 3.0% or less. The thickness ratio of the A layer can be controlled by the extrusion conditions among the film-forming conditions. In the present invention, the thickness ratio of the A layer can be calculated by the method described below.
[0061] The thickness of the polyarylene sulfide film of the present invention is not particularly limited, but from the perspective of film-forming properties, 10 to 150 μm is preferred, 20 to 125 μm is more preferred, and 25 to 100 μm is more preferred.
[0062] Regarding the method for manufacturing a polyarylene sulfide film of the present invention, a method for manufacturing a film using a polyphenylene sulfide resin (hereinafter abbreviated as PPS resin) as a polyarylene sulfide-based resin is described as an example, but the present invention is not limited to this example.
[0063] Sodium sulfide and p-dichlorobenzene are combined and reacted under high temperature and high pressure in an amide-based polar solvent such as N-methyl-2-pyrrolidone (NMP). If necessary, copolymer components such as m-dichlorobenzene or trihalobenzene may also be included. Potassium hydroxide or an alkali metal carboxylate salt is added as a degree of polymerization modifier, and the polymerization reaction is carried out at 230–290°C. After polymerization, the polymer is cooled, and the polymer is filtered as a water slurry to obtain a wet granular polymer. An amide-based polar solvent is added to this granular polymer and washed by stirring at a temperature of 30–100°C, then washed several times with ion-exchanged water at 30–80°C, and washed several times with an aqueous solution of a metal salt such as calcium acetate, and then dried to obtain a polyphenylene sulfide polymer powder.
[0064] In the present invention, when cleaning the polymer powder, the obtained polymer powder is subjected to a cleaning treatment in an NMP solvent at a temperature of 100 to 200°C for 6 to 24 hours, and then washed several times with pure water at 30 to 80°C to obtain the polymer powder (cleaning completed). This polymer powder is fed into a vent-equipped extruder and melt-extruded into a strand, cooled with water at a temperature of 25°C, and then cut to produce a chip, which is then made into a PPS chip.
[0065] A master batch is prepared by mixing the polymer powder obtained above as a polyarylene sulfide-based resin and / or polymer powder (cleaned) with inorganic particles and / or other thermoplastic resin (X), etc., in any proportion. In the present invention, the method of preparing the master batch is preferably a method of forming a master batch using a device that applies shear stress, such as a twin-screw extruder. In this case, it is preferable to knead in the mixing section such that the resin temperature range is from the melting point of the PAS-based resin (I) + 5°C to 80°C, more preferably from the melting point of the PAS-based resin (I) + 10°C to 80°C, and even more preferably from the melting point of the PAS-based resin (I) + 15°C to 70°C. In addition, it is preferable to set the screw rotation speed to a range of 100 rpm to 1500 rpm. By setting the resin temperature or screw rotation speed to a preferred range, the dispersion diameter of the dispersed phase can be controlled.
[0066] In the present invention, first, if necessary, a PPS chip dried under reduced pressure at 180°C for 3 hours and a master batch are mixed in a predetermined ratio, supplied to a full-flight single-axis extruder with a melting section set to 300-350°C, passed through a filter, and then discharged from a T-die type die. Then, while applying an electrostatic charge to a cooling drum with a surface temperature of 20-70°C, the mixture is rapidly cooled and solidified to obtain a substantially unoriented unoriented film. In the case of a laminated film of two or more layers, the two types of chips are supplied to separate melt extrusion devices and heated above the melting point of each resin. Each raw material, melted by heating, is laminated in a molten state into a junction device installed between a melt extrusion device and a die outlet, in a 2-layer structure in which PPS is the main component and at least one other thermoplastic resin different from PPS is the main component, or into a 3-layer structure in which PPS is the main component and at least one other thermoplastic resin different from PPS is the main component, or into a 3-layer structure in which PPS is the main component and at least one other thermoplastic resin different from PPS is the main component, at an arbitrary lamination ratio (e.g., 0.3:24.4:0.3 or 0.3:24.7), and then extruded from a die outlet on a slit. This sheet-like material is placed in close contact with the PPS layer facing the cooling drum on a cooling drum with a surface temperature of 20 to 70°C and cooled to solidify, thereby obtaining a substantially non-oriented 2-layer laminated sheet or 3-layer laminated sheet.
[0067] Next, in the case of biaxial stretching, the unoriented film obtained above is biaxially stretched using a sequential biaxial stretching machine or a simultaneous biaxial stretching machine in a range above the glass transition point (Tg) of the polyarylene sulfide resin and below the cold crystallization temperature (Tcc), and then a biaxially oriented film is obtained by performing a single or multi-stage heat treatment at a temperature in the range of 150 to 280°C. As a stretching method, a sequential biaxial stretching method (a stretching method combining stretching in one direction, such as stretching in the length direction followed by stretching in the width direction), a simultaneous biaxial stretching method (a method of stretching in the length direction and the width direction simultaneously), or a method combining the same may be used. Here, a sequential biaxial stretching method is exemplified in which stretching is performed first in the length direction and then in the width direction.
[0068] The unoriented film is heated with a group of heating rolls and stretched in the longitudinal direction (MD direction) by 2.0 to 4.5 times, more preferably 2.8 to 4.2 times, in one or more stages (MD stretching). The stretching temperature is in the range of Tg to Tcc, preferably (Tg+5) to (Tcc-10)℃. Afterward, it is cooled with a group of cooling rolls at 20 to 50℃.
[0069] As a method for stretching in the width direction (TD direction) following MD stretching, for example, a tenter is commonly used. Both ends of the film are gripped with clips and guided to a tenter to perform stretching in the width direction (TD stretching). The stretching temperature is preferably in the range of Tg to Tcc, and more preferably in the range of (Tg+5) to (Tcc-10)°C. From the perspective of the flatness of the film, the stretching ratio is preferably 3.0 to 5.0 times, and more preferably 3.0 to 4.5 times.
[0070] Next, the stretched film is subjected to a heat-setting operation (heat-setting treatment) under tension. The heat-setting treatment is performed in a single or multi-stage heat treatment at a temperature in the range of 150 to 280°C, and the film is cooled to room temperature, and if necessary, while performing a relaxation treatment in the length and width directions, and then wound to obtain a biaxially oriented polyarylene sulfide film.
[0071] In the present invention, when a cleaning treatment is performed on a film, the obtained polyarylene sulfide film is cleaned in a solvent of NMP at a temperature of 100 to 200°C for 5 to 30 hours, and then cleaned 3 to 5 times with pure water at 30 to 80°C to obtain the polyarylene sulfide film of the present invention.
[0072] The polyarylene sulfide film of the present invention is suitable for use as an automotive component, a battery component, and an electrical and electronic material, in particular as various components requiring transparency and industrial packaging materials, such as a protective material for the bottom plate of a flexible printed circuit board, and a capacitor material requiring surface quality, as it has excellent transparency and color tone and excellent runability and quality of the film surface.
[0073] In addition, the polyarylene sulfide film of the present invention may be coated with various coating agents on both sides or one side in-line or offline for purposes such as improving weather resistance or adhesion, or surface protection.
[0074] A circuit board is fabricated by forming a conductive film on the polyarylene sulfide film obtained in this manner. When used as a transparent circuit, the conductive film is preferably a transparent or translucent conductor, and examples include a metal film such as an Ag film, a metal oxide film such as an ITO (indium tin oxide) film, and a resin film containing conductive fine particles, which are laminated together. The method of forming the conductor is a well-known method, such as sputtering or paste printing, but is not particularly limited. The patterning of the circuit board is a well-known method, such as etching by photolithography or screen printing. Additionally, if necessary, through holes are formed using a drill, laser, or melt penetration method to obtain the circuit board.
[0075] A circuit board using the polyarylene sulfide film of the present invention is useful as a transparent antenna substrate due to its excellent transparency and color tone.
[0076] [Method of measuring characteristics]
[0077] (1) Light transmittance at wavelengths of 550 nm, 400 nm, and 600 nm
[0078] Measurements were taken using the device below, and the light transmittance at each wavelength was calculated from the following formula.
[0079] Device: UV meter U-3410 (manufactured by Hitachi High-Tech Corporation)
[0080] Wavelength range: 300 nm to 800 nm
[0081] Measurement speed: 120 nm / min
[0082] Measurement Mode: Transmission
[0083] Light transmittance (%) = (Tr1 / Tr0) × 100
[0084] However, Tr1 is the intensity of light passing through the sample, and Tr0 is the intensity of light passing through air at the same distance except that it does not pass through the sample.
[0085] (2) Yellowness (b value)
[0086] The three stimulus values X, Y, and Z were measured using the transmission method according to JIS-Z-8722 (2000) with a spectroscopic colorimeter CM-3600d (manufactured by Konica Minolta Holdings). Then, the lightness (L value) and the yellowness (b value) of the Hunter Lab color system were calculated using the following formula.
[0087] b value = 7.0 × (Y - 0.847 × Z) / Y1 / 2
[0088] (3) Surface roughness (SRa)
[0089] Average centerline roughness (SRa) was calculated using the Surfcorder ET30HK manufactured by Kosaka Laboratory Ltd. under the following conditions.
[0090] Stylus curvature radius: 2㎛
[0091] Cutoff: 0.25 mm
[0092] Measurement length: 0.5 mm
[0093] Measurement interval: 5㎛
[0094] Number of measurements: 40
[0095] (4) Depth volume (Vv), number of protrusions (n)
[0096] Measurements were performed using the VertScan 2.0 R5300GL-Lite-AC manufactured by Mitsubishi Chemical Systems, Inc., and the captured image was surface-corrected by a polynomial fourth-order approximation using the attached analysis software, and the depth volume (Vv) and number of protrusions (n) were calculated with a threshold of 0 nm. The measurement conditions are as follows. Measurements were performed on both sides of the film with n=100 for each side, and the average values were used as the depth volume (Vv) and number of protrusions (n) for each side. For Examples 26 and 52, measurements were performed on the surface of layer A with n=100, and the average values were used as the depth volume (Vv) and number of protrusions (n) for each side.
[0097] Manufacturer: Mitsubishi Chemical Systems, Inc.
[0098] Device Name: VertScan 2.0 R5300GL-Lite-AC
[0099] Measurement conditions: CCD camera SONY HR-57 1 / 2 inch
[0100] Objective: 5x
[0101] Intermediate lens: 0.5x
[0102] Wavelength filter: 530 nm white
[0103] Measurement Mode: Wave
[0104] Measurement software: VS-Measure Version 5.5.1
[0105] Analysis Software: VS-Viewer Version 5.5.1
[0106] Measurement area: 0.561 mm × 0.561 mm
[0107] (5) Glossiness
[0108] The average value of five data points measured on the film surface under conditions of an incident angle of 60° and a reception angle of 60° using a digital angle-changing gloss meter UGV-5D manufactured by Suga Test Instruments Co., Ltd. in accordance with JIS K-7105 (1981) was defined as the gloss (%). Measurements were performed on both sides of the film, and the values of the surfaces with high gloss were listed in the table.
[0109] (6) Fourier transform infrared spectroscopy (FT-IR)
[0110] A Frontier FT-IR manufactured by PerkinElmer Japan Co., Ltd. is used, along with an UATR IR unit, and spectral intensity is measured by the attenuated total reflection (ATR) method with a diamond / ZnSe crystal medium. The resolution of the spectrometer is 1 cm⁻¹. -1The spectrum is measured with an integrated count of 16. Spectral intensity is defined as the absorbance (arb.unit) at each wavelength. When measuring the spectrum of the surface layer of a film, the surface layer of the film is brought into close contact with a medium crystal to perform the measurement. Contact between the medium crystal and the sample is achieved by applying pressure using a jig on the device. Pressure is increased while observing the spectrum of the sample, and the measurement is performed at the point where the spectral shape no longer changes due to the pressure. Spectral intensity is determined as the absorbance (arb.unit) at each wavelength.
[0111] In the present invention, in the case of a single-layer film, 1145 cm from the infrared absorption spectrum obtained by performing a measurement by the above method from one of the surfaces -1 ~1160 cm -1 The presence or absence of an absorption peak between them is determined. In the case of a laminated film, the presence or absence of an absorption peak is determined by measuring from the surface of the outermost layer constituting Layer A using the above method. If the laminated configuration is unclear, the presence or absence of an absorption peak is determined by measuring from both surfaces using the above method.
[0112] (7) Scanning electron microscope (SEM) observation of the cross-section
[0113] After embedding the film in epoxy resin, the film cross-section was cut using a microtome in directions parallel to the length and perpendicular to the film plane without crushing the film in the thickness direction. Subsequently, the cut film cross-section was fixed to the sample stage of a scanning electron microscope under conditions where material degradation due to heat would not occur, and cross-sectional ion milling was performed using the IM4000PLUS ion milling device manufactured by Hitachi High-Tech Corporation, followed by Pt deposition. The obtained film cross-section was then observed using the JSM-6700F electrolytic scanning electron microscope manufactured by JEOL, Ltd. under conditions of an acceleration voltage of 3.0 kV and a working distance of 8.0 mm to obtain images.
[0114] (7-1) Void formation rate of particles and dispersions
[0115] To calculate the void formation rate of particles and dispersions, images obtained by observing under conditions of an observation magnification of 30,000 times were analyzed. Additionally, the observation location was randomly selected at the position where particles or dispersions are observed on the cross-section of the film, but the vertical direction of the image was parallel to the thickness direction of the film, and the horizontal direction of the image was parallel to the film plane direction.
[0116] For the obtained observations, image analysis software (MacView ver 4.0 manufactured by Mountech Co., Ltd.) was used to calculate the area of each particle (D1), the area of the dispersion (D1'), the area of the void surrounding the particle (D2), and the area of the void surrounding the dispersion (D2'). It was determined that if the area of D2 was 10% or more of the area of D1, it was a particle forming a void, and if the area of D2' was 10% or more of the area of D1', it was a dispersion forming a void. For evaluation, 100 points were measured for each particle and dispersion, and the void formation ratio was calculated from the number of particles and dispersions that formed voids.
[0117] Void formation ratio = (Number of void-forming particles + Number of void-forming dispersed particles) / Measurement score (200 points) × 100
[0118] (7-2) Major axis and aspect ratio of the dispersion
[0119] The major axis and aspect ratio of the dispersions were determined by analyzing images obtained from observations at an observation magnification of 30,000x. The obtained observation images were introduced as images into an image analyzer (Leica Application Suite LAS ver 4.6, manufactured by Leica Microsystems GmbH), 20 random dispersions were selected, and the circumscribed circles of each dispersion were taken and the average value of their diameters was used as the size of the dispersions. Additionally, the major and minor axes of the dispersions were read to calculate the aspect ratios.
[0120] (7-3) Lamination thickness of layer A and lamination ratio of layer A
[0121] The stacking thickness of layer A and the stacking ratio of layer A were observed under conditions of an observation magnification of 5000x, and the thickness of layer A of the film was measured at 5 random points from the analysis of the obtained image, and the average value was taken as the layer thickness of layer A.
[0122] In addition, the total thickness of the film was observed under conditions of an observation magnification of 3000x, and an image was taken that allows observation of the entire thickness direction of the film. The total thickness of the film was measured from the image obtained by observation. If the entire thickness direction of the film could not be confirmed at the above magnification, several images were taken in the thickness direction, and the entire image was confirmed by connecting the images. A total of five arbitrary locations were selected as samples to be used for thickness measurement, and the average of the measurement values of the five samples was taken as the film thickness of that sample.
[0123] (8) Transparency
[0124] White dots with diameters decreasing by 10㎛ in increments from 200㎛ to 10㎛ are printed on a black drawing paper. Each film is overlapped on the black drawing paper, and the diameter of the white dot visible from the top of the film is judged according to the following criteria. C was judged to have poor transparency.
[0125] AA: Visible down to 10㎛ (Excellent transparency)
[0126] A: Visible down to 50㎛ (good transparency)
[0127] B: Visible down to 100㎛ (moderate transparency)
[0128] C: Invisible even at 100㎛ (poor transparency)
[0129] (9) Color tone
[0130] Color samples were created on a white drawing paper by changing the RGB color model at a dot with a diameter of 0.5 mm. Color samples were printed by increasing the B value by 10 from R (Red) 255, G (Green) 255, B (Blue) 0 to R255, G255, B250. Each film was placed on the white drawing paper, and the color dot was judged based on the following criteria to see if it was visible from a position 100 cm from the top of the film. D was judged to have a color tone defect.
[0131] AA: Allows visibility of R255, G255, B240 or higher (excellent hue)
[0132] A: Visible up to R255, G255, B230 (Good hue)
[0133] B: Visible up to R255, G255, and B200 (hue is inferior)
[0134] C: Visible up to R255, G255, B180 (difficulty with hue)
[0135] D: Visible up to R255, G255, B170 (significant difficulties with hue)
[0136] (10) Driving performance
[0137] Using a friction measuring instrument manufactured by TOYO SEIKIKOGYO CO., LTD., the initial upward resistance value was measured in accordance with ASTM-D1894 (1999) by overlapping the film so that one side and its reverse side were in contact and rubbing them against each other in the MD direction, and the maximum value was set as the static friction coefficient μs. However, if the initial rise was too large and exceeded the upper limit of the measurement value (5.0), the measurement was deemed impossible. The samples were made into rectangles with a width of 80 mm and a length of 200 mm, and 5 sets (10 sheets) were cut out. 5 measurements were performed, and the average value was calculated. Runability was judged based on the following criteria from the calculated static friction coefficient. D was judged as poor runability.
[0138] A: μs=0.50 or less (Good driving performance)
[0139] B: μs exceeds 0.50 and is 0.60 or less (average drivability)
[0140] C: μs exceeding 0.60 and 0.70 or less (driving performance is slightly inferior)
[0141] D: Exceeds μs=0.70 (Drivability is poor)
[0142] (11) Surface quality
[0143] A light from an LED light source was shone on a film of 1 m², scratches on the surface visible by the transmitted light were counted, and the surface quality was determined based on the following criteria from the number of scratches in the 1 m² area.
[0144] AA: Less than 50 pieces / ㎡
[0145] A: 50 units / ㎡ or more, less than 100 units / ㎡
[0146] B: 100 units / ㎡ or more, less than 150 units / ㎡
[0147] C: 150 units / ㎡ or more, less than 200 units / ㎡
[0148] D: 200 pieces / ㎡ or more
[0149] (Example)
[0150] (Reference Example 1) Method for manufacturing PPS resin (granules)
[0151] 1.00 mol of 47% sodium hydrosulfide, 1.03 mol of 96% sodium hydroxide, 1.65 mol of N-methyl-2-pyrrolidone (NMP), 0.45 mol of sodium acetate, and 150 g of ion-exchanged water were injected into a 1-liter autoclave equipped with a process stirrer, and the mixture was slowly heated to 225°C over approximately 3 hours while stirring at 240 rpm and passing nitrogen through at atmospheric pressure, and after 211 g of water and 4 g of NMP were discharged, the reaction vessel was cooled to 160°C.
[0152] Next, 1.00 mole of p-dichlorobenzene (p-DCB) and 1.31 mole of NMP were added. The reaction vessel was then sealed under nitrogen gas. While stirring at 240 rpm, the temperature was raised from 200°C to 235°C at a rate of 0.6°C / min, and after reaching 235°C, the reaction was continued at 235°C for 95 minutes. Afterward, the temperature was raised to 270°C at a rate of 0.8°C / min and maintained for 100 minutes. After reaching 270°C, 1 mole of water was injected into the system over 15 minutes. After 100 minutes at 270°C, the temperature was cooled to 200°C at a rate of 1.0°C / min, and then rapidly cooled to near room temperature. The contents were withdrawn, diluted with 0.4 liters of NMP, stirred at 85°C for 30 minutes, and then the solvent and solids were separated by filtration through a sieve (80 mesh). Following the post-processing step, 0.5 liters of NMP were added to the obtained solid, stirred at 85°C for 30 minutes, and then filtered. The obtained solid was washed three times with 0.9 liters of hot water and filtered. Additionally, 1 liter of hot water was added to the obtained particles, washed twice, and filtered to obtain polymer particles. This was dried with hot air at 80°C and then dried under reduced pressure at 120°C to obtain polyphenylene sulfide (PPS) resin granules (PPS granules) having a melting point of 280°C and a mass average molecular weight of 70,000.
[0153] (Reference Example 2) Method for manufacturing PPS pellets
[0154] The PPS resin (granules) prepared in Reference Example 1 was fed into a co-rotating twin-screw kneading extruder equipped with a vent and heated to 320°C, melt-extruded to be discharged in a strand, cooled with water at a temperature of 25°C, and then immediately cut to produce PPS pellet 1.
[0155] (Reference Example 3) Preparation of PPS granules and thermoplastic resin master pellets (MB1)
[0156] A vented twin-screw kneading extruder of the co-rotation type, having one kneading paddle kneading section, was heated to 320°C, and 90 parts by mass of PPS granules obtained in Reference Example 1 and 10 parts by mass of polyethersulfone (PESU: Solvay Ltd., VERADEL 3600) were supplied from the feed port, and after melt kneading at a screw rotation speed of 200 rpm, the mixture was discharged in the form of a strand, cooled with water at a temperature of 25°C, and then immediately cut to produce a master pellet (MB1) containing 10 parts by mass of PESU.
[0157] (Reference Example 4) Preparation of PPS granules and a master pellet (MB2) of particles
[0158] A particle masterbatch (MB2) with a particle content of 10 mass% was prepared in the same manner as in Reference Example 3, except that a mixture of 90 mass% of the PPS resin (granules) prepared in Reference Example 1 and 10 mass% of calcium carbonate (average particle diameter 1.0 μm) as an inert particle was melt-kneaded.
[0159] (Reference Example 5) Preparation of PPS granules and thermoplastic resin master pellets (MB3)
[0160] A vented twin-screw kneading extruder of the co-rotation type, having one kneading paddle kneading section, was heated to 320°C, and 90 parts by mass of PPS granules obtained in Reference Example 1 and 10 parts by mass of polyphenylsulfone (PPSU: Solvay Ltd., RADEL R5600-NT) were supplied from the feed port, and after melt kneading at a screw rotation speed of 200 rpm, the mixture was discharged in the form of a strand, cooled with water at a temperature of 25°C, and then immediately cut to produce a master pellet (MB3) containing 10 parts by mass of PPSU.
[0161] (Examples 1–12)
[0162] The PPS resin (granules) prepared in Reference Example 1 was subjected to washing treatment using NMP as a solvent under the conditions shown in Table 1-1, and washed three times with pure water at a temperature of 40°C to obtain PPS granules (washed). These PPS granules (washed) were fed into a co-rotating twin-screw kneading extruder equipped with a vent and heated to 320°C, melt-extruded to be discharged in a strand, cooled with water at a temperature of 25°C, and then immediately cut to produce PPS pellets (washed).
[0163] PPS pellets (washed) and PPS master pellets were mixed uniformly in the ratio shown in Table 1, dried under reduced pressure at 180°C for 3 hours, and then fed into a single-screw extruder with the molten portion heated to 315°C.
[0164] Next, the molten polymer was passed through a fiber-sintered stainless steel filter (20 μm cutting) and melt-extruded from a T-die set to a temperature of 310°C. Subsequently, an unoriented film with a thickness of 350 μm was obtained by contact cooling and solidification while applying an electrostatic charge to a cast drum with a surface temperature of 25°C. Next, the obtained unoriented film was stretched in the longitudinal direction of the film at a magnification of 3.5 times at a stretching temperature of 105°C using a longitudinal stretching machine consisting of a group of heated rolls, utilizing the difference in peripheral speeds of the rolls. Afterward, both ends of the film were supported by clips and guided to a tenter to be stretched in the width direction of the film at a magnification of 3.5 times at a stretching temperature of 100°C. Subsequently, heat treatment was performed at 280°C followed by a 2% relaxation treatment, and after cooling to room temperature, the film edges were removed to obtain a polyarylene sulfide film with a thickness of 25 μm. The physical properties and characteristics of the obtained film are shown in Table 1-1.
[0165] (Example 13)
[0166] A polyarylene sulfide film was obtained in the same manner as in Example 1, except that a washing treatment was not performed on the PPS resin (granules).
[0167] (Example 14)
[0168] A polyarylene sulfide film was obtained in the same manner as in Example 1, except that the PPS resin (granules) was supplied as PPS pellets only without washing treatment.
[0169] (Comparative Example 1)
[0170] A polyarylene sulfide film was obtained in the same manner as in Example 1, except that PPS pellet 1 and master batch were mixed to have the composition and ratio of Table 1-1 and a washing treatment was performed according to the conditions shown in Table 1-1.
[0171] (Comparative Example 2)
[0172] A polyarylene sulfide film was obtained in the same manner as in Example 1, except that the PPS resin (granules) was not subjected to washing treatment and only PPS pellet 1 was used, and a master batch was mixed with PPS pellet 1 to have the composition and ratio of Table 1-1.
[0173] (Examples 15–25)
[0174] The PPS resin (granules) prepared in Reference Example 1 was subjected to washing treatment using NMP as a solvent under the conditions shown in Table 1-2, and washed three times with pure water at a temperature of 40°C to obtain PPS granules (washed). These PPS granules (washed) were fed into a co-rotating twin-screw kneading extruder equipped with a vent and heated to 320°C, melt-extruded to be discharged in the form of a strand, cooled with water at a temperature of 25°C, and then immediately cut to produce PPS pellets (washed).
[0175] Raw materials for layers A and B were prepared such that PPS pellets (cleaned) and PPS master pellets had the composition and ratio shown in Table 1-2. Each raw material was vacuum dried individually at 180°C for 3 hours, then individually supplied to two single-sided extruders heated to 315°C. In a molten state, the lamination ratio was induced in a lamination device located above the die to form three layers (lamination configuration A / B / A) as shown in Table 1-2. The materials were then discharged from a T-die type die and subjected to close quenching and solidification while applying an electrostatic charge to a cast drum with a surface temperature of 25°C to obtain an unoriented film with a thickness of 350 μm. Subsequently, the obtained unoriented film was stretched using a longitudinal stretching machine consisting of a group of heated rolls, utilizing the difference in peripheral speed of the rolls, at a stretching temperature of 105°C, at a magnification of 3.5 times in the longitudinal direction of the film. Afterward, both ends of the film were supported with clips and guided to a tenter, whereby the film was stretched at a stretching temperature of 100°C at a magnification of 3.5 times in the width direction. Subsequently, heat treatment was performed at 280°C, followed by a 2% relaxation treatment. After cooling to room temperature, the film edges were removed to obtain a polyarylene sulfide film with a thickness of 25 μm. The physical properties and characteristics of the obtained film are shown in Table 1-1.
[0176] (Example 26)
[0177] A polyarylene sulfide film was obtained in the same manner as in Example 16, except that the lamination configuration of the lamination device was set to A / B 2 layers and the lamination ratio was set as shown in Table 1-2.
[0178] (Example 27)
[0179] A polyarylene sulfide film was obtained in the same manner as in Example 16, except that the PPS resin (granules) was not subjected to washing treatment and was used as PPS pellet 1.
[0180] (Comparative Example 3)
[0181] A polyarylene sulfide film was obtained in the same manner as in Example 15, except that the raw materials were supplied to have the composition and ratio shown in Table 1-2.
[0182] (Examples 28~39)
[0183] PPS pellet 1 and PPS master pellet were mixed uniformly in the ratio shown in Table 2-1, dried under reduced pressure at 180°C for 3 hours, and then supplied to a single-axis extruder with the molten portion heated to 315°C. Subsequently, the molten polymer was passed through a fiber-sintered stainless steel filter (20 µm cutting) and melt-extruded from a T-die set to a temperature of 310°C. Then, an unoriented film with a thickness of 350 µm was obtained by contact cooling and solidification while applying an electrostatic charge to a cast drum with a surface temperature of 25°C. Subsequently, the obtained unoriented film was stretched in the longitudinal direction of the film at a 3.5-fold ratio using a longitudinal stretcher consisting of a group of heated rolls and utilizing the difference in peripheral speed of the rolls at a stretching temperature of 105°C. After that, both ends of the film were supported by clips and guided to a tenter, and stretched in the width direction of the film at a 3.5-fold ratio at a stretching temperature of 100°C. After continuing heat treatment at 280°C, a 2% relaxation treatment was performed, and after cooling to room temperature, the film edge was removed to obtain a polyarylene sulfide film with a thickness of 25 μm.
[0184] The obtained film was subjected to cleaning treatment using NMP as a cleaning solvent under the conditions shown in Table 2-1, and washed five times with pure water at a temperature of 40°C to obtain a cleaned polyarylene sulfide film. The physical properties and characteristics of the obtained film are shown in Table 2-1.
[0185] (Comparative Example 4)
[0186] A polyarylene sulfide film was obtained in the same manner as in Example 28, except that PPS pellet 1 and master batch were mixed to have the composition and ratio of Table 2-1 and a washing treatment was performed under the conditions shown in Table 2-1.
[0187] (Examples 40~50)
[0188] The raw materials for layers A and B were prepared such that PPS pellet 1 and PPS master pellet had the composition and ratio shown in Table 2-2. Each raw material was vacuum dried individually at 180°C for 3 hours, then individually supplied to two single-axis extruders heated to 315°C. In a molten state, the materials were induced in a lamination device located above the die to have a lamination ratio of 3 layers (lamination configuration A / B / A) as shown in Table 2-2. The materials were then discharged from a T-die type die and subjected to close quenching and solidification while applying an electrostatic charge to a cast drum with a surface temperature of 25°C to obtain an unoriented film with a thickness of 350 μm. Subsequently, the obtained unoriented film was stretched using a longitudinal stretching machine consisting of a group of heated rolls, utilizing the difference in peripheral speed of the rolls, at a stretching temperature of 105°C, at a magnification of 3.5 times in the longitudinal direction of the film. Afterward, both ends of the film were supported with clips and guided to a tenter, whereby it was stretched at a stretching temperature of 100°C in the width direction of the film at a magnification of 3.5 times. Subsequently, heat treatment was performed at 280°C, followed by a 2% relaxation treatment. After cooling to room temperature, the film edges were removed to obtain a polyarylene sulfide film with a thickness of 25 μm.
[0189] The obtained film was subjected to cleaning treatment using NMP as a cleaning solvent under the conditions shown in Table 2-2, and washed five times with pure water at a temperature of 40°C to obtain a cleaned polyarylene sulfide film. The physical properties and characteristics of the obtained film are shown in Table 2-2.
[0190] (Example 51)
[0191] A polyarylene sulfide film was obtained in the same manner as in Example 41, except that the lamination configuration of the lamination device was set to A / B 2 layers and the lamination ratio was set as shown in Table 2-2.
[0192] (Comparative Example 5)
[0193] A polyarylene sulfide film was obtained in the same manner as in Example 41, except that the raw materials were supplied to have the composition and ratio shown in Table 2-2.
[0194] [Table 1-1]
[0195]
[0196] [Table 1-2]
[0197]
[0198] [Table 2-1]
[0199]
[0200] [Table 2-2]
[0201]
[0202] (Industrial Applicability)
[0203] The polyarylene sulfide film of the present invention can be suitably used as a transparent circuit substrate or a transparent antenna substrate due to its excellent transparency and color tone.
Claims
Claim 1 A polyarylene sulfide film having a polyarylene sulfide (PAS)-based resin as the main component, a spectral light transmittance Ta of 75% or more at a wavelength of 550 nm, a b value of 5.0 or less, and a surface roughness (Ra) of at least one film surface of 10 nm or more and 200 nm or less. Claim 2 A polyarylene sulfide film having a b value of 3.0 or less in claim 1. Claim 3 A polyarylene sulfide film according to claim 1 or 2, wherein the spectral light transmittance Tb at a wavelength of 400 nm and the spectral light transmittance Tc at 600 nm satisfy the following formula (i). Tc-Tb ≤ 8.2% Formula (i) Claim 4 delete Claim 5 In claim 1 or 2, the depth volume (Vv) from the reference surface on at least one film surface is 50 μm 3 800㎛ or more 3 Polyarylene sulfide film. Claim 6 A polyarylene sulfide film according to claim 1 or 2, wherein the depth volume (Vv) and the number of protrusions (n) from a reference plane on at least one film surface satisfy the following formula (iii). 0.01 ≤ Vv / n ≤ 3.0 Formula (iii) Claim 7 A polyarylene sulfide film according to claim 1 or 2, wherein the glossiness of at least one film surface is 140% or more and less than 200%. Claim 8 A polyarylene sulfide film according to claim 1 or 2, containing particles and / or a dispersion, wherein the void formation ratio of said particles and dispersion is 10% or less. Claim 9 In claim 1 or 2, 1145 cm⁻¹ in the infrared absorption spectrum obtained by Fourier transform infrared spectroscopy (FT-IR). -1 ~1160 cm -1 Polyarylene sulfide film having at least one absorption peak between them. Claim 10 A polyarylene sulfide film according to claim 1 or 2, having two or more layers having a polyarylene sulfide-based resin as the main component, wherein at least one outermost layer is a layer (layer A) having a polyarylene sulfide-based resin as the main component and containing at least one other thermoplastic resin (X) that is different from the polyarylene sulfide-based resin. Claim 11 A polyarylene sulfide film according to claim 1 or 2, having three or more layers having a polyarylene sulfide-based resin as the main component, wherein the outermost layer of both sides has a polyarylene sulfide-based resin as the main component and a layer (layer A) containing at least one other thermoplastic resin (X) that is different from the polyarylene sulfide-based resin. Claim 12 In claim 10, the infrared absorption spectrum of the A layer obtained by Fourier Transform Infrared Spectroscopy (FT-IR) is 1145 cm⁻¹ -1 ~1160 cm -1 Polyarylene sulfide film having at least one absorption peak between them. Claim 13 In claim 10, a different thermoplastic resin (X) different from the polyarylene sulfide resin is incompatible with the polyarylene sulfide resin, and a polyarylene sulfide film comprising the different thermoplastic resin (X) different from the polyarylene sulfide resin as a dispersion in the polyarylene sulfide resin. Claim 14 A polyarylene sulfide film according to claim 13, wherein the aspect ratio of the dispersion is 5.0 or higher and 15.0 or lower, and the major axis of the dispersion is 200 to 2000 nm. Claim 15 In claim 10, a polyarylene sulfide film in which the thickness ratio of the A layer is 0.1% or more and 10% or less with respect to the total thickness of the film. Claim 16 A polyarylene sulfide film used in a transparent circuit substrate according to claim 1 or 2. Claim 17 A polyarylene sulfide film used in a transparent antenna substrate according to claim 1 or 2.
Citation Information
Patent Citations
Polyphenylene sulfide film roll for deposition and capacitor
JP2004153206A
Polyphenylene sulfide film and its manufacturing method
JP2004231909A
Polyarylene sulfide
JP2009138206A
Biaxially oriented polyarylene sulfide film
JP2011089110A
Polyarylene sulfide-based composition
JP2017088690A